2022
DOI: 10.1002/anie.202200778
|View full text |Cite
|
Sign up to set email alerts
|

Short Guanidinium‐Functionalized Poly(2‐oxazoline)s Displaying Potent Therapeutic Efficacy on Drug‐Resistant Fungal Infections

Abstract: New antifungals are urgently needed to combat invasive fungal infections, due to limited types of available antifungal drugs and frequently encountered side effects, as well as the quick emergence of drug‐resistance. We previously developed amine‐pendent poly(2‐oxazoline)s (POXs) as synthetic mimics of host defense peptides (HDPs) to have antibacterial properties, but with poor antifungal activity. Hereby, we report the finding of short guanidinium‐pendent POXs, inspired by cell‐penetrating peptides, as synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 57 publications
2
70
0
Order By: Relevance
“…We then designed and synthesized a series of guanidinium‐pendent poly(2‐oxazoline)s by cationic ring open polymerization of 2‐oxazoline monomers, followed by guanidinylation modification (Figure 9a) [25a] . The obtained poly(2‐oxazoline)s with different chain lengths ranging from 5–20 subunits showed narrow dispersity (Figure 9b).…”
Section: Introductionmentioning
confidence: 99%
“…We then designed and synthesized a series of guanidinium‐pendent poly(2‐oxazoline)s by cationic ring open polymerization of 2‐oxazoline monomers, followed by guanidinylation modification (Figure 9a) [25a] . The obtained poly(2‐oxazoline)s with different chain lengths ranging from 5–20 subunits showed narrow dispersity (Figure 9b).…”
Section: Introductionmentioning
confidence: 99%
“…33,[33][34][35][36][37][38][39] For primary amine expression in the side chain, the preferred strategy encompasses the polymerization of tert-butyloxycarbonyl (BOC) protected amine-containing 2-oxazolines and their subsequent deprotection by trifluoroacetic acid (TFA). 29,[40][41][42] As for post polymerization modifications, orthogonally reactive monomers such as alkenes 43,44 and alkynes 45 can be selected to engage in click chemistries to attach the amine of choice. Display of secondary amines in the side chains can also be fashioned by hydrolysis of the oxazoline repeating units resulting in polyethyleneimine (PEI).…”
Section: Introductionmentioning
confidence: 99%
“…albicans and C. neoformans were greatly enhanced after guanidination . Liu et al reported that the antifungal activities of hyperbranched polylysines (HPLs) against Candida were increased by up to 32-fold when the amine groups were guanylated …”
Section: Introductionmentioning
confidence: 99%
“…33 Jiang et al found that the antifungal activities of poly(2-oxazoline)s against C. albicans and C. neoformans were greatly enhanced after guanidination. 34 Liu et al reported that the antifungal activities of hyperbranched polylysines (HPLs) against Candida were increased by up to 32-fold when the amine groups were guanylated. 35 In this paper, a series of α-PLns and guanylated α-PLn (α-PLn-Gxs, where x denotes the percentage of guanylation of amine groups) are successfully synthesized.…”
Section: ■ Introductionmentioning
confidence: 99%